Response of rapeseed fatty acid composition to foliar application of humic acid under different plant densities - Mohammad Amiri; Amir Hossein Shirani Rad; Alireza Valadabadi; Saeed Sayfzadeh; Hamidreza Zakerin (Plant, Soil and Environment, 2020)
In order to the assessment of humic acid application on the qualitative characteristics of rapeseed in various plant densities, a factorial split-plot test was conducted for two cultivation years in Karaj, Iran. In this experiment, plant density considered in three levels (40, 60, and 80 plants/m2), humic acid at two concentrations (non-application and application at the concentration of 0.3%) in the main plots, and six cultivars of rapeseed embracing RGS003, Zafar, Julius, Jerry, Zabol10, and Hyola4815 in the sub-plots. The interaction effect of plant density ×humic acid × cultivar on seed yield, oil yield, oleic acid, linolenic acid, linoleic acid, palmitic acid, erucic acid, canopy temperature, and seed glucosinolate content as well as the interaction effect of plant density × cultivar on the oil content and total chlorophyll content were significant at 1% level. Cv. Jerry had the maximum seed and oil yields under humic acid application condition with the density of 40 plants/m2, and the maximum contents of oleic, linoleic, and palmitic fatty acids as well. Moreover, this cultivar, through containing the lower and standard content of erucic acid and glucosinolate, is recommendable under the circumstance of the present research.